Association between exposure to terpene compounds and risk of metabolic syndrome: exploring the potential mediating role of inflammatory response - Nie, Jiyu; Huang, Zhizhuo; Wen, Lin; Li, Haiying; Xie, Qianqian; Wang, Houchun; Lai, Zhengtian; Lin, Chuhang; Jing, Chunxia (Frontiers in Endocrinology, 2025)
BackgroundTerpenes are potentially harmful substances that are associated with endocrine disruption due to their ability to produce oxidizers, aldehydes, and secondary aerosol particles. However, the exact association between terpenoids and metabolic syndrome remains unclear.ObjectiveThis study aims to examine the relationship between individual and mixed exposure to terpene compounds and the risk of developing metabolic syndrome.MethodsWe utilized data from the NHANES 2013-2014 cycle, including 1,135 participants. Multiple regression models, Bayesian kernel regression (BKMR), and quantile g calculation (QGC) were employed to assess the association between individual and mixed terpene exposure and metabolic syndrome. Additionally, a mediation analysis was performed to explore potential biological pathways mediated by inflammation, using the Advanced Cancer Inflammation Index as a metric.ResultsThe regression analysis indicated a positive association between exposure to limonene and metabolic syndrome (OR (95%):1.74(1.17, 2.57), p=0.005). The BKMR regression and the QGC model showed a positive association between exposure to mixed terpenes and the increased risk of metabolic syndrome (p=0.001). Subgroup analyses within the BKMR revealed significant positive trends among males, individuals under 60, and the overweight groups. Furthermore, exposure to mixed terpenes exhibited positive trends with lower HDL levels(p<0.000). The Advanced Cancer Inflammation Index was identified as a potential mediator of the positive correlation between α-pinene, β-pinene, and metabolic syndrome.ConclusionsThis study suggests that exposure to both individual and mixed terpenes may increase risk of developing metabolic syndrome. However, further longitudinal studies are imperative to establish causality between terpene compounds and the risk of metabolic syndrome.